AB0240 Are rheumatologists capable to assess chest x-ray for intertitial lung disease related with rheumatoid arthritis and systemic sclerosis?. (23rd January 2014) - Kilic, L.; Kalyoncu, U.; Ariyurek, M.; Bilgen, S.; Karadag, O.; Akdogan, A.; Kiraz, S.; Tunceli, E.; Hayran, M.; Ertenli, I.
Abstract : Background: Guideline of intertitial lung disease (ILD) recommend history, physical examination, chest X-ray and blood tests for assesment of ILD in the first step 1 . Objectives: To assess accuracy of chest X-ray for connective tissue disease related ILD. Methods: In our hospital, PACS (Picture archiving and communication system) system present since 2009. Rheumatoid arthritis (RA) or systemic sclerosis (SSc) patients enrolled to study. In first step, patients who had computerized tomography and chest X-ray in PACS were screened. Of 163 patients (126 (77.3%) RA and 37 (22.7%) SSc) had both imaging in PACS. Sixtyeight (41.5%) patients had ILD in CT. An intern doctor put in order file number of all patients. Two rheumatologist (2 and 9 years experience) and one pulmonary radiologist (18 years experience) assesed all chest X-ray separetly. Physicians were informed sex and age of patients. Physicians also known that some of the patients had ILD and others not. Physicians and radiologist assessed chest X-Ray as "definitive", "suspected" or "absent" for ILD. CT results were used as gold standard. Kendall's tau-b statistics were used by "definitive" plus "suspected" versus "absent". Results: Thirtyseven of 163 (22.7%) patients were male. Among rheumatologist, "definitive" ILD concordance was 0.63 (standart error (SE) 0.071). For both diseases, CT concordance of radiologist, 2 and 9 years experience rheumatologist were %53.2 (SE:6.0), %30.4 (SE:7.2), %32.2 (SE: 7.1). Sensitivity of "definitive" ILD by chest X-ray of 2 and 9 experience rheumatologist and radiologist were 44.9%, 41.9% and 47.8% respectively. Conclusions: Rheumatologists detected truely definitive/suspected ILD by chest X-Ray. However, spesificity of evaluation of rheumatologist very low than radiologist. Negative predictive value of chest X-ray is acceptable for RA but not for SSc. Rheumatologist seems to capable for detection of ILD by chest X-Ray in first step evaluation. References: Thorax. 2008;63 Suppl 5:v1-58. Disclosure of Interest: None Declared